Pemanfaatan Toga Sebagai Apotek Hidup dalam Meningkatkan Kemandirian Kesehatan Keluarga - Wachidah Fauziyanti; Ariyani Indriastuti; Marhamah Marhamah; Penta Widyartati; Sri Wiranti Setyanti (Jurnal Informasi Pengabdian Masyarakat, 2026)
The utilization of Family Medicinal Plants (TOGA) as a living pharmacy in home gardens represents a community empowerment strategy to enhance family health independence based on local resources. The main problem faced by the community was the limited knowledge regarding the types, benefits, cultivation, and processing of TOGA. This community service program aimed to improve community knowledge, skills, and awareness through educational and participatory approaches. The methods included socialization, training on cultivation and processing of medicinal plants, and evaluation using pre-test and post-test instruments based on a Likert scale (1–4). The evaluation results indicated a significant improvement across all indicators, with the average pre-test score of 2.13 increasing to 3.63 in the post-test, reflecting an improvement of 1.50 points. The highest improvement was observed in the indicators related to plant maintenance and simple traditional medicine processing. These findings demonstrate that socialization and practical training effectively enhanced community capacity and encouraged behavioral change toward family health independence. Therefore, the utilization of TOGA as a living pharmacy can serve as a sustainable health solution grounded in local wisdom.